Paediatric Crohn Disease: Disease Activity and Growth in the BELCRO Cohort After 3 Years Follow-up. Issue 2 (August 2016) - De Greef, Elisabeth; Hoffman, Ilse; Smets, Francoise; Van Biervliet, Stephanie; Bontems, Patrick; Hauser, Bruno; Paquot, Isabelle; Alliet, Philippe; Arts, Wim; Dewit, Olivier; De Vos, Martine; Baert, Filip; et al.
ABSTRACT: Objective: The Belgian registry for paediatric Crohn disease (BELCRO) cohort is a prospective, multicentre registry for newly diagnosed paediatric patients with Crohn disease (CD) (<18 years) recruited from 2008 to 2010 to identify predictive factors for disease activity and growth. Methods: Data from the BELCRO database were evaluated at diagnosis, 24 and 36 months follow-up. Results: At month 36 (M36), data were available on 84 of the 98 patients included at diagnosis. Disease activity evolved as follows: inactive 5% to 70%, mild 19% to 24%, and moderate to severe 76% to 6%. None of the variables such as age, sex, diagnostic delay, type of treatment, disease location, disease activity at diagnosis, and growth were associated with disease activity at M36. Paediatricians studied significantly less patients with active disease at M36 compared with adult physicians. Sixty percent of the patients had biologicals as part of their treatment at M36. Adult gastroenterologists initiated biologicals significantly earlier. They were the only factor determining biologicals' initiation, not disease location or disease severity at diagnosis. Median body mass index (BMI) z score evolved from −0.97 (range −5.5–2.1) to 0.11 (range −3.4–2) and median height z score from −0.15 (range −3.4–1.6) to 0.12 (range −2.3–2.3) at M36. None of the variables mentioned above influenced growth over time. Conclusions: Present treatment strategies lead to good disease control in the BELCRO cohort after 3 years. Logistic regression analysis did not show any influence of disease location or present treatment strategy on disease activity and growth, but patients under paediatric care had significantly less severe disease at M36.